2019
DOI: 10.1002/jcb.28737
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of REDD1 attenuates oxygen glucose deprivation/reoxygenation‐evoked ischemic injury in neuron by suppressing mTOR‐mediated excessive autophagy

Abstract: Cerebral ischemia/reperfusion (I/R) typically occurs after mechanical thrombectomy to treat ischemic stroke, generation of reactive oxygen species (ROS) after reperfusion may result in neuronal insult, ultimately leading to disability and death. Regulated in development and DNA damage responses 1 (REDD1) is a conserved stress response protein under various pathogenic conditions. Recent research confirms the controversial role of REDD1 in injury processes. Nevertheless, the role of REDD1 in cerebral I/R remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In our study, ginsenoside Re treatment increased the mRNA level of GLUT1, suggesting that ginsenoside Re improves energy metabolism in cardiomyocytes following H/R. REDD1 is an essential regulator of cell growth, and a low level of REDD1 expression is associated with cell apoptosis (Sun and Yue, 2019). Our study showed that ginsenoside Re treatment significantly increased the mRNA level of REDD1, indicating that the effects of ginsenoside Re on cardiomyocyte H/R injury are related to the inhibition of cell apoptosis.…”
supporting
confidence: 60%
“…In our study, ginsenoside Re treatment increased the mRNA level of GLUT1, suggesting that ginsenoside Re improves energy metabolism in cardiomyocytes following H/R. REDD1 is an essential regulator of cell growth, and a low level of REDD1 expression is associated with cell apoptosis (Sun and Yue, 2019). Our study showed that ginsenoside Re treatment significantly increased the mRNA level of REDD1, indicating that the effects of ginsenoside Re on cardiomyocyte H/R injury are related to the inhibition of cell apoptosis.…”
supporting
confidence: 60%
“…Despite tremendous advances in the theoretical understanding of ischemic stroke in the past several decades, stroke remains the third leading cause of death and permanent disability [35]. Oxygen glucose deprivation reperfusion is an in vitro model that mimics the in vivo process of a series of pathological reactions initiated by ischemia-reperfusion [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…However, on the other hand, with the continuous enhancement of autophagy, it can directly induce the death of oxidized cells and further damage to mitochondria, thereby reversely aggravating the oxidative stress damage of cells 29 . By monitoring the levels of autophagy proteins LC3II/I, Beclin1 and P62, we found that MPP + increased the autophagy level, and pre-treatment with ART decreased the autophagy level compared with MPP + .…”
Section: Discussionmentioning
confidence: 99%